From Nascent Research Ideas to Emergent Grounded Theory – a Novice Researcher’s Reflections on the Grounded Theory Process - Harrison, Helen (International Journal of Qualitative Research, 2025)
The problem addressed in this paper relates to the challenges faced by a researcher re-engaging with the academic world after an absence of many years. My recent re-entry to this arena followed twenty-plus years of immersion in the international development sector and the exploration of academic opportunities as a new direction that could enhance my international work. My re-engagement in research included challenges that are perhaps slightly different from those who have followed the more conventional academic route. The purpose of this paper is to reflect on my journey of re-engagement with research at a doctoral level, in the hopes that it might bring insights that can be of use to other novice researchers as they journey on their academic path. The method used in my research was that of grounded theory in an overseas context, with open-structured interviews as the data collection tool, and women refugees as the research participants. The findings of this paper, therefore, reflect on pursuing a research study within that context as a novice researcher and draw out some relevant points of learning and reflection. The implications of these findings can be of particular use to readers who identify as novice Grounded Theory (GT) students, supervisors of novice GT researchers, or other qualitative researchers yet to determine their methodological route. There are also insights to be shared relating to carrying out overseas research and conducting research in a way that places the voices of the participants in the foreground.